2005
DOI: 10.4028/www.scientific.net/msf.488-489.849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strong Magnetic Field on the Discontinuous and Continuous Precipitation in AZ91 Mg Alloy

Abstract: A strong static magnetic field (SSMF) of about 10 T was introduced to the aging process of AZ91 magnesium alloy. Comparing with conventional aging, in the first stage of aging with SSMF, discontinuous precipitation of Mg17Al12 at grain boundary was accelerated. The magnetically induced grain boundary migration might be responsible for this acceleration effect. The density of the Mg17Al12 continuous precipitates inside the grains was increased and the precipitation plates became thinner in SSMF pre-aged specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Among various kinds of magnetic field, static magnetic field has also been found to exert influence on metallurgical phenomena such as grain boundary migration [3,4], formation of texture [5,6] and phase transformation [7][8][9]. In many of these metallurgical processes, diffusion of atoms in the material is of great importance as it acts as the controlling factor in processes like homogenization and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Among various kinds of magnetic field, static magnetic field has also been found to exert influence on metallurgical phenomena such as grain boundary migration [3,4], formation of texture [5,6] and phase transformation [7][8][9]. In many of these metallurgical processes, diffusion of atoms in the material is of great importance as it acts as the controlling factor in processes like homogenization and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that the dislocation motion can be easily activated under uniform magnetic field in the absence of any detectable external mechanical action [17,18]. While an enhancement of the precipitation reactions in a Mg alloy was already reported for the case of a strong, about 12 T, magnetic field [9], the present results reveal a significant impact of low-or moderate-intensity magnetic fields, of 0.7 T, on the decomposition kinetics of the supersaturated solid solution in generally diamagnetic Cu-Be-Ni alloy.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, texture and microstructure evolution in cold-rolled Al or Zr were found to be affected by a magnetic field, too [7,8]. Dong with co-workers [9] have investigated the influence of a static magnetic field of 10 T during aging of the magnesium alloy AZ91. An enhancement of discontinuous precipitation of the intermetallic phase Mg 17 Al 12 at grain boundaries was observed, alongside with a retardation of volume diffusion rates.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of researches have been carried out to investigate the influence of magnetic field on metallurgical phenomena such as grain boundary migration [1,2], precipitation [3], and phase transformation [4].…”
Section: Introductionmentioning
confidence: 99%